Analisis Penataan dan Pengelolaan Informasi Arsip Kaset Pita pada Museum Musik Indonesia Berdasarkan Sistem Klasifikasi Geografis Terstruktur - Moch.Rizaldi Hasan; Halid Hasan; Nunung Aliyati Fajer (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Archives, as information recorded in various media, including cassette tapes, hold significant historical, cultural, and commercial value. These materials are classified as audiovisual archives. Among them, cassette tapes containing national and international songs form part of the collection at the Museum Musik Indonesia, located in Malang, East Java, Indonesia. As a self-managed museum run by a community of music enthusiasts, the Museum Musik Indonesia provides public access to information about its song collections. Given the large number of cassette tapes preserved, an effective information arrangement system is essential. This study recommends the use of a geographical classification system to organize the collection. Archive data is entered into a database using Microsoft Excel, allowing for structured cataloging and easier retrieval. This research employs a qualitative method, involving interviews with several informants from the Museum Musik Indonesia. The findings indicate that applying a geographical classification system in organizing cassette tape archives significantly improves the museum’s management capabilities. This system facilitates the rediscovery of archived items, enhances organization, and supports accurate record-keeping. Furthermore, electronic storage of archive information reduces the risk of data loss and ensures long-term preservation. The implementation of this arrangement not only benefits internal management but also enhances the quality of service provided to museum visitors. By enabling quicker and more accurate access to the collection, the museum can offer a richer and more engaging visitor experience. This study demonstrates that systematic archival practices, even when implemented with accessible tools like Microsoft Excel, can yield substantial benefits in cultural heritage preservation. The approach can serve as a reference for other small-scale or community-based museums seeking efficient, low-cost methods for managing and safeguarding their archival assets.